Plant sterols: Friend or foe in CNS disorders?. (April 2015) - Vanmierlo, Tim; Bogie, Jeroen F.J.; Mailleux, Jo; Vanmol, Jasmine; Lütjohann, Dieter; Mulder, Monique; Hendriks, Jerome J.A.
Abstract: In mammals, the central nervous system (CNS) is the most cholesterol rich organ by weight. Cholesterol metabolism is tightly regulated in the CNS and all cholesterol available is synthesized in situ. Deficits in cholesterol homeostasis at the level of synthesis, transport, or catabolism result in severe disorders featured by neurological disability. Recent studies indicate that a disturbed cholesterol metabolism is involved in CNS disorders, such as Alzheimer's disease (AD), multiple sclerosis (MS), and amyotrophic lateral sclerosis (ALS). In contrast to circulating cholesterol, dietary plant sterols, can cross the blood–brain barrier and accumulate in the membranes of CNS cells. Plant sterols are well-known for their ability to lower circulating cholesterol levels. The finding that they gain access to the CNS has fueled research focusing on the physiological roles of plant sterols in the healthy and diseased CNS. To date, both beneficial and detrimental effects of plant sterols on CNS disorders are defined. In this review, we discuss recent findings regarding the impact of plant sterols on homeostatic and pathogenic processes in the CNS, and elaborate on the therapeutic potential of plant sterols in CNS disorders.